A clinical case of a patient with left atrial myxoma and obstructive coronary atherosclerosis - Ludhmila, Kalatsei; Shafran, Mohamed; Hafeel, Aysha; De Silva, Pumudu (International Journal of Research in Medical Sciences, 2024)
A 74-year-old patient, who was under examination, presented several symptoms, including weakness, cough, rapid heartbeat, tenderness and pain behind the sternum. With the help of transthoracic and transoesophageal echocardiography the patient was diagnosed with left atrial myxoma. When coronary angiography was performed, the patient was diagnosed with obstructive coronary atherosclerosis, including occlusion of left anterior descending artery and 75% stenosis of right coronary artery. After confirmation of the diagnosis patient underwent surgery, which included CABG and excision of myxoma in left atrium. Although the patient experienced some postoperative complications such as post cardiotomy syndrome, bilateral hydrothorax, mild anaemia and left lung pneumonia, she was discharged from the hospital with a stable condition. The patient was also given several recommendations to help overcome her complications, including dietary changes, wearing a chest compressor brace, and taking several medications, including antiplatelet agents, diuretics, beta-blockers and ARBs.